Competition-based Learning Strategy of the Online Introductory Accounting Quiz for Non-accounting Majors - Radzi, Afaf Izzati Nafhah; Awang Drahman, Dayang Nazari; Joseph, Corina; Rahmat, Mariam; Suria, Khadijah (International Business Education Journal, 2020)
In colleges and universities, competition-based learning strategy is one of the ways used by instructors to overcome students’ challenges in their learning process. An investigation on the non-accounting major students’ perception on participating in the online accounting quiz competition for the Introduction to Financial Accounting and Reporting course has been carried out. The questionnaire was specifically developed and distributed to students from the Diploma in Computer Science, Diploma in Public Administration, Diploma in Tourism Management and Diploma in Office Management and Technology programs of Universiti Teknologi MARA, Sarawak Branch, who underwent the course in Semester March 2018. Descriptive statistics were performed to achieve the objective of this paper. Overall, the respondents and participants have mixed feelings that the online quiz was effective for learning in an accounting course. The Competition-based Learning strategy explains that the non-accounting students intend to get the certificate from the involvement in the online quiz competition. The limitations and future research opportunities are also provided in this paper.